Boot Camp Approach to Surgical Training (Springer International Publishing, 2018)
This book provides a unique opportunity to gain a complete overview of how to run orthopedic surgery training, with all aspects of course planning covered including schedules, objectives, feasibility, instructors, materials, division-specific sessions, evaluations, research and refining course content. This practical program guide offers key information and course structuring guidance sought by orthopaedic specialists who wish to enhance their training programs for residents. Boot Camp Approach to Surgical Training will be a go-to book for both trainers and trainees wishing to successfully plan or complete a surgical education. In addition to surgical trainers and trainees, program directors in medical education, simulation lab directors, educators and researchers in medical training will find this book to be an essential resource for planning effective competency-based courses in orthopaedic surgery. .